Odpowiedź:
[tex]\huge\boxed{\dfrac{6x^2+5x-6}{4x^2-9}=\dfrac{3x-2}{2x-3},\ x\in\mathbb{R}-\left\{\pm\dfrac{3}{2}\right\}}[/tex]
Szczegółowe wyjaśnienie:
[tex]\dfrac{6x^2+5x-6}{4x^2-9}[/tex]
Dziedzina wyrażenia:
[tex]4x^2-9\neq0\qquad|+9\\4x^2\neq9\qquad|:4\\x^2\neq\dfrac{9}{4}\to x\neq\pm\sqrt{\dfrac{9}{4}}\\\\x\neq\pm\dfrac{3}{2}\\\\\boxed{x\in\mathbb{R}-\left\{-\dfrac{3}{2},\ \dfrac{3}{2}\right\}}[/tex]
[tex]\dfrac{6x^2+5x-6}{4x^2-9}=\dfrac{6x^2+9x-4x-6}{(2x)^2-3^2}=\dfrac{3x(2x+3)-2(2x+3)}{(2x-3)(2x+3)}\\\\=\dfrac{(2x+3)(3x-2)}{(2x-3)(2x+3)}=\dfrac{3x-2}{2x-3}[/tex]